Prevention of Cataracts by Statins: A Meta-Analysis. (March 2014) - Kostis, John B.; Dobrzynski, Jeanne M.
Background: Current data indicate a persisting concern about possible cataractogenecity of statins. Objective: To perform a meta-analysis of studies pertaining to statins and cataract. Methods: We identified 363 records by a systematic search of the MedLine, Web of Knowledge, Cochrane database, and ClinicalTrials.gov. After exclusion of duplicates, studies without cataract as an outcome, reviews, and animal or basic science studies, we analyzed 14 studies. Two end points were examined: clinical cataract (requiring extraction or reported by the patient) and lens opacities discovered by slit-lamp examination. Results: Using random effects meta-analysis, a statistically significant decrease in cataracts with statins was observed among studies examining clinical cataract (odds ratio [OR] 0.81, 95% confidence interval [CI] 0.71-0.93, P = .0022). Absolute risk reduction was 1.4% ± 0.015%, 95% CI 1.1%-1.7%, P < .0001, corresponding to 71, 95% CI 59-91, number needed to treat. The effect was larger for the harder end point of cataract extraction (OR 0.66, 95% CI 0.61-0.71, P < .0001). Metaregression indicated an increase in benefit with longer duration of statin use with OR varying from 0.54 for a treatment duration of 14 years to 0.95 for a treatment duration of 6 months. Older age was associated with lower benefit (OR 1.03 for persons in their 70s to OR 0.49 for persons in their 40s), and there were no differences by gender. Several sensitivity analyses confirmed the results. Limitations of this analysis include the combination of randomized and observational studies and imprecise ascertainment of exposure and incomplete adjustment for confounders in several observational studies. Conclusion: This meta-analysis indicates a clinically relevant protective effect of statins in preventing cataracts. The effect is more pronounced in younger patients and with longer duration of follow-up, while there is no difference by gender.